Is the Energy Expenditure Provided by Exergames Valid? - Viana, Ricardo Borges; Gentil, Paulo; Andrade, Marília Santos; Vancini, Rodrigo Luiz; de Lira, Claudio Andre Barbosa (International Journal of Sports Medicine, 2019)
To assess energy expenditure (EE) estimated by a metabolic system during the exergame Hollywood Workout on Xbox 360Kinect® and to compare this measure with the EE estimated by the exergame (EEEx). thirty-four physically active young males performed the Sports Athlete protocol of the Hollywood Workout. Oxygen uptake (V̇O2) and carbon dioxide production (V̇CO2) were measured before and during the protocol using a metabolic system. The absolute means V̇O2 and V̇CO2 were used to calculate the EE during the exergame session (EEMS). The EEEx (kcal) provided by the exergame was collected, and the two measures were compared. Mean V̇CO2 and V̇O2 during the Sports Athlete protocol were 1.8±0.4 L·min−1 (22.9±3.2 mL·kg−1.min−1) and 2.0±0.4 L·m−1 (25.4±2.6 mL·kg−1·min−1), respectively. The EEMS (300.3±53.4 kcal) was 88.6±34.7% greater than the EEEx (160.3±16.5 kcal; p<0.0001; d=3.7 [large effect size]). The EEMS was almost double EEEx. Thus, it is necessary to use caution when using EE information provided by an exergame interface. Further, future studies need to evaluate EE provided by other exergames. The companies that produce the games must be more attentive and adopt more precise methods in order to provide more accurate information to the users.
Keywords: physiological responses; oxygen uptake; Kinect®; exercise